Transportation risk management: One company's approach. Issue 3 (16th September 2016) - Lutostansky, Elizabeth; Miller, Gary; Dennehy, Martin
Abstract : Air Products has a long history in process safety risk management. The company evaluates the risk of transporting hazardous substances in addition to its risk assessments for fixed sites and pipelines. The Center for Chemical Process Safety (CCPS) book, Guidelines for Chemical Transportation Risk Analysis, has been used as the starting point for the Air Products approach to this subject. Over the past few years, the company has refined its transportation assessment methodology and calculation tools and has established a work process where the businesses and supply chains are integrated into the transportation risk analysis (TRA) process. The purpose of this article is to summarize Air Products' TRA process, including criteria for deciding if TRA is required, selection of release scenarios considered in a TRA, assumptions made regarding populations and weather conditions and the overall risk review process. An example risk analysis will be presented. Comments on the comparison of TRA with pipeline TRA will also be provided. © 2016 American Institute of Chemical Engineers Process Saf Prog 36: 252–256, 2017